Administration in ancient India: An introductory outline - Tyagi, Ruchi (2010)
Original historical and archaeological sources along with the voluminous traditional literature from the Vedic period. Buddhist and Jain texts, the Puranic literature and the writings of Panini, Kautilya, Patanjali, Megasthenese, Fahien and Huen-Tsang, etc. offer a dependable account of administration in ancient India. This article presents a critical and comparative study of the important aspects of polity and public administration in that period. Drawing mainly on these sources it portrays structure of government, bureaucracies, provincial and district administration, revenue and criminal justice system. - Reproduced.
Keywords: Public administration; Public administration